PENERAPAN STRATEGI PROMOSI PRODUK UNGGULAN PADA KANTOR DINAS KOPERASI USAHA MIKRO KECIL DAN MENENGAH KABUPATEN BENGKALIS - Dewi Puspasari; Try Handayani; Dwi Astuti (Politeknik Negeri Bengkalis, 2015)
Abstract: The purpose of this research are to know how the application of promotion strategy at the department of cooperation small and mediun scaled- business of bengkalis regency, To know the constraints faced in the implementation of promotion strategy at the department of cooperation small and mediun scaled-business of bengkalis regency, To find solutions to what is done to deal with the obstacles in the implementation of promotion strategy at the department of cooperation small and mediun scaled-business of Bengkalis regency. the location of this thesis in the department of cooperation small and mediun scaled-business of (UMKM) Bengkalis regency. object of studyis taken from the department of cooperation small and mediun scaled-business of (UMKM) Bengkalis regency. This research is Descriptive metodology, qualitative research studies. the implementation of (UMKM) promotion strategy of Bengkalis regency. Organize activities expo exhibition in several cities, Cooperate with the company / other agencies, Implement promotionl activities through the medium of television RTV Bengkalis, constraints facedthe implementation of promotion strategy at the department of cooperation Issue improper budget time, Time exhibition is not timely, solutions faced To Overcome Obstacles Inthe application of promotionstrategyDoing temporary loans to certain financial institutions, Lots of unexpected costs in the field, time is not timely exhibition. Keywords : Promotion Strategy, Small and Mediun Scaled Business.